Pengaruh Return On Invesment (ROI) dan Earning Per Share (EPS) terhadap Harga Saham pada Perusahaan Otomotif yang Terdaftar di Bursa Efek Indonesia - Wahyu Indah Mursalini (Jurnal Kajian Akuntansi dan Auditing, 2020)
Information earning per share of a company’s net profit shows the company is ready to share to the shareholders of the company. ROI and EPS is part of the profitability ratios. This study aimed to examine the effect of Return On Investment and Earning Per Share to the stock price on the automotive company listed on the Indonesia Stock Exchange. The population in this study is the automotive company which is listed on the Indonesia Stock Exchange during the period 2014 to 2018. The sample is determined based on purposive sampling method in order to obtain six samples of the company. Data used is secondary data obtained from www.idx.co.id. The analytical method used is the classic assumption test, Tarbelt regression, t-test, f and the coefficient of determination.Based on analysis of partial significance level of 5%, then the results of this study concluded: (1) Return On Investment affect the prices of shares with a value of 3.089 t count > t table 2.052 with significant value 0,005 < α 0,05, (2 ) Earning PerShare on stock price with the t value of 1.586 < t table 2,052 with significant value0,127 > α 0.05.And test results f where earnings and cash flows simultaneous effect on the price of shares with a value of F 5.885228 with probability (Prob. F-Statistik) with the value 0,000. And the coefficient of determination (R2) of 0.652 or 65.2% of profit and cash flows affect stock prices, 34.8% are influenced by other factors not examined in this study among other things, sales grwoth, debt, and net profit margin.